2000
DOI: 10.1093/sleep/23.6.1f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleep Loss on Waking Actigraphy

Abstract: The validity of actigraphy to make this distinction relative to polysomnography depends on several factors, including the population being studied and the time-of-day. In healthy, normal young, and middle-age adults sleeping at night, the agreement between actigrahpic and polysomnographic assessment of sleep time is generally 90% and better. 1 In contrast, in the elderly and patients with sleep disorders, the percent agreement generally is less, sometimes 80% or lower. 1 The discrepancy is in both directions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 7 publications
1
16
1
Order By: Relevance
“…It also confirms that the actiwatch is able to detect the effects of a hypnotic on actigraphically measured sleep. Moreover this study, following the recommendation of Roehrs and colleagues [24], adds further evidence that actigraphy can provide a reliable and sensitive indication of the time course of action of psychoactive drugs. Studies using actigraphy to measure the effects of other psychoactive compounds and drug groups in both subject and patient populations both in the laboratory and in field studies will be necessary to further validate this method as a useful tool in psychopharmacology.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…It also confirms that the actiwatch is able to detect the effects of a hypnotic on actigraphically measured sleep. Moreover this study, following the recommendation of Roehrs and colleagues [24], adds further evidence that actigraphy can provide a reliable and sensitive indication of the time course of action of psychoactive drugs. Studies using actigraphy to measure the effects of other psychoactive compounds and drug groups in both subject and patient populations both in the laboratory and in field studies will be necessary to further validate this method as a useful tool in psychopharmacology.…”
Section: Discussionmentioning
confidence: 52%
“…Whilst some authors [22,24,29] have reported that the derived actigraph data show significant reductions in activity after dosing with various compounds, a variety of times blocks have been used ranging from 6 to 24 h. Although this has provided an indication that actigraphy may be able to detect changes in behavioural activity due to the effects of medication, the use of these large analysis time frames may not be sufficient to provide a discrete profile of the drug and of its time course of effect on activity and pharmacodynamics. A study on the effects of several antihistamines in comparison to placebo [33], however, has provided evidence that by using the AMI 32 actigraph (Ambulatory Monitoring Inc., New York, USA) it is possible to show significant changes in actigraphically measured activity up to 6 h post dose with promethazine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of these studies confirm that data derived from the sleep/wake detection algorithm can accurately reflect the rise and fall of daytime sedation (Alford et al, 2000;Stanley and Hindmarch, 2001). Roehrs et al (2000) used waking actigraphy to investigate the effects of reduced time in bed and the sedating effects of the first generation antihistamine diphenhydramine (50 mg). Seventeen young adult subjects (6 males, 11 females) completed the study which consisted of four treatment periods placebo-8 h TIB, placebo-4 h TIB, placebo 0 h TIB and diphenhydramine 50 mg 8 h TIB.…”
Section: The Measurement Of Daytime Sedationmentioning
confidence: 99%